Directive Speech Acts In Umar Bin Khattab's Speech When He Was Appointed As Caliph: A Pragmatics Study - Anjani, Fuji Fitri; Nugraha, Tubagus Chaeru; Ardiati, Riza Lupi (Devotion : Journal of Research and Community Service, 2024)
This study discusses the directive act of directive speech delivered by Umar bin Khattab, which aims to influence the thoughts and actions of Muslims. This study uses a descriptive-analytical method with a qualitative approach, aiming to describe and interpret the data as it is. The data collection method used is the listening method with the free listening technique (SBC) and the recording technique. The collected data was then analyzed using a matching method and a pragmatic sorting technique, and an analysis of the strategies based on the theory of Brown and Levinson (1987). The results of this study identified 34 utterances containing directive speech acts in the five speeches of Umar bin Khattab, which are categorized into 9 requests, 18 commands, 3 requesting attention, 1 prohibition, and 1 type of warning.